Overexpression of JAM-A in non-small cell lung cancer correlates with tumor progression. - Min Zhang; Wenting Luo; Bo Huang; Zihui Liu; Limei Sun; Qingfu Zhang; Xueshan Qiu; Ke Xu; Enhua Wang (PLoS ONE, 2013)
The objective of the current study was to determine the clinical significance of junctional adhesion molecule A (JAM-A) in patients with non-small cell lung cancer (NSCLC) and the biological function of JAM-A in NSCLC cell lines. We showed that JAM-A is predominantly expressed in cell membranes and high expression of JAM-A occurred in 37% of lung tumor specimens compared to corresponding normal tissues. High expression of JAM-A was significantly correlated with TNM stage (P = 0.021), lymph node metastasis (P = 0.007), and decreased overall survival (P = 0.02), In addition, we observed that silencing JAM-A by small interfering RNA inhibited tumor cell proliferation and induced cell cycle arrest at the G1/S boundary. Western blotting analysis revealed that knockdown of JAM-A decreased the protein levels of cyclin D1, CDK4, 6, and P-Rb. Thus, JAM-A plays an important role in NSCLC progression.